Application of Data Visualization Technology in Water Resources Management Based on Cesium - LE Shihua; DONG Jing; ZHANG Xu; LIU Weilin; TIAN Chunsi; LI Yifan; WU Zhiming; LIU Delong (Renmin Zhujiang)
Three-dimensional virtual simulation technology is widely used in the fields of digital earth,digital city,digital watershed,etc.It is more conducive for scientific researchers to gain insight into the laws of the scientific data by using the visualization technology in the simulation system.However,the representation of scientific data is more dependent on professional visualization software in practical applications,which leads to its separation from the existing simulation system.In view of this,this paper systematically introduces the related technical principles and the implementation methods of visualization technology,such as heat maps,scalar visualization of water depth,projected texture transformation,meteorological cloud map drawing,water depth contours and isosurface real-time rendering,and effectively integrates a variety of technologies in the Cesium-based 3D simulation platform.The results show that the final display frame rate of each technology is greater than 30 fps so that it can meet the requirements of real-time display,and smooth screen.Based on the technology,the data representation form of the original system is enriched,and a strong basis for large-capacity scientific computing and real-time display is obtained.Therefore,it is expected to be more widely used in virtual reality and scientific visualization.